Craft specialization in Hellenistic-Roman Cyprus: identity or habitus? - Winther-Jacobsen, Kristina (Rei Cretariae Romanae Fautorum Acta, 2015)
The two main ways we differentiate ourselves and others in material culture is either through quantity of artefacts or through the endless variability of artefacts over space and time leading to choices between appropriate and inappropriate behaviour. Artefacts are produced and used by people not only for physical tasks but to mediate social, economic and political relationships and to create, express, and maintain social, economic and political identities. Consequently, material culture seems the ideal source material for the study of identity. The past twenty years focus on agency in archaeology has sparked an enormous interest in identity. Yet, the correlation between artefact and identity is very complex Framing our research questions in social theory is a great challenge. This article aims to discuss further the difficulties of applying social theory to the study of material culture in the past.